Coronavirus hits former-Soviet countries - S. S. Zhiltsov (Проблемы постсоветского пространства, 2020)
The year of 2020 started a new chapter in the development of former-Soviet countries. The coronavirus epidemic, which began in the Chinese city of Wuhan, has spread to affect all countries throughout the world, including the countries of the former Soviet Union. Its influence has already affected the economic and social development of the countries in the post-Soviet space. Closing borders, stopping tourism, and imposing severe restrictions on transport services were the first measures that contributed to reducing the incidence rates. At the same time, these measures affected bilateral and multilateral trade and economic relations among the countries of the post-Soviet space.All countries of the post-Soviet space have taken steps to allocate additional funds to combat coronavirus. Ad hoc funds were formed, the review of budget expenditures and revenues began. However, in fact in the first few months the countries faced economic distress, the overcoming of which could take considerable time.The coronavirus epidemic is taking place against the backdrop of global economic crisis and a sharp drop in oil prices. Economic development models based on increasing consumption without economic growth, increasing the level of external and internal debt have shown their insolvency. In these conditions, the countries of the post-Soviet space, which are highly dependent on the external factor, have also experienced significant economic hardships.Finally, the «price warfare» in the oil market has a strong influence. The United States and Saudi Arabia’s attempts to achieve dominance in the oil market, by displacing Russia from it, as well, have had a destabilizing impact on the world oil market. This factor has had a direct impact on those former-Soviet countries that produce and export hydrocarbon resources.In general, the coronavirus epidemic, taking place against the backdrop of global economic challenges and oil competition, will have a negative impact on the economic and political development of former-Soviet countries. The impact of the epidemic, its consequences, will affect the former-Soviet countries for many years to come.